Karakteristik Obstruction of Justice dalam Penyidikan Korupsi : Menguji Batas Imunitas Profesi Advokat - Muhammad Iqbal Al-Azizi; Aisyah Putri Salsabila; Mauliyanti Salsabila; Musleh Harry (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Corruption cases are often accompanied by acts of obstruction of justice that hinder law enforcement processes. Problems arise when such acts are committed by advocates who possess professional immunity rights. This study aims to analyze the characteristics of obstruction of justice in corruption investigations and the limits of advocates’ immunity. This normative legal research employs statutory and conceptual approaches. The findings show that obstruction of justice is characterized by intent, active interference with legal proceedings, actions beyond professional duties and a direct connection to corruption cases. Professional immunity is functional and does not apply when advocates obstruct law enforcement.